Do local bank branches reduce SME credit constraints? Evidence from public-private bank interaction - Anders Gustafsson; Agostino Manduchi; Andreas Stephan (Research Institute of Industrial Economics (IFN), 2019)
In the past few decades, commercial banks have substantially reduced the number of their branch offices. We address the question of whether or not the increased distance from the lenders correspondingly faced by many small and medium sized enterprises (SMEs) translates into a lower volume of loans. We use a unique dataset on loans from a state owned Swedish bank designed to support credit-constrained SMEs and interact their loan portfolio with the number of nearby commercial bank offices at the firm level along with an IV strategy to account for endogeneity. The estimation results strongly indicate that a larger number of local bank offices increases the local credit supply, and decreases the credit constraints of nearby SMEs.
Keywords: L52; O38; H81; L26; G28; 330; Credit constraints; Relationship banking; State owned bank; Small business